ANALISIS PEMBERDAYAAN MASYARAKAT MENUJU PENGEMBANGAN DESA WISATA “NOYO GIMBAL VIEW” DESA BANGSRI KECAMATAN JEPON KABUPATEN BLORA - Malis Furaida; Yuwanto Yuwanto (Journal of Politic and Government Studies, 2026)
Tourism village development is a local potential-based development strategy that positions the community as the primary actor in improving the welfare and sustainability of tourism. The Noyo Gimbal View Tourism Village in Bangsri Village, Jepon District, Blora Regency, has developed through the utilization of natural resources, agriculture, culinary arts, and innovative cultural activities supported by the use of digital media. This study aims to analyze the process of community empowerment and the forms of community participation in the development of this tourism village. The method used is descriptive qualitative research with data collection techniques through interviews, observation, and documentation. The results of the study indicate that the community empowerment process in the Noyo Gimbal View Bangsri Tourism Village was implemented through three main stages, namely the socialization or awareness stage, the capacity transformation stage, and the independence stage. In the socialization stage, the community was given an understanding of the village's potential and the concept of a tourism village. The capacity transformation stage was realized through various forms of training and mentoring to increase community capacity in tourism management, services, and the use of digital technology. The independence stage was marked by the increasing ability of the community to manage tourism businesses independently and sustainably. Community participation in the development of the tourism village was seen in the form of labor contributions, involvement in the management of tourism businesses, and support for ideas and concepts in organizing tourism activities. Overall, community empowerment and participation in the Noyo Gimbal View Bangsri Tourism Village played an important role in encouraging the success of tourism village development, improving the community's economy, and strengthening the sustainability of tourism village management based on local potential.